Revision of the genus Turris Batsch, 1789 (Gastropoda: Conoidea: Turridae) with the description of six new species - Kilburn, Richard N.; Fedosov, Alexander E.; Olivera, Baldomero M. (Zootaxa, 2012)
The taxonomy of the genus Turris Batsch, 1789, type genus of the family Turridae, widespread in shallow-water habitatsof tropic Indo-Pacific, is revised. A total of 31 species of Turris, are here recognized as valid. New species described: Tur-ris chaldaea, Turris clausifossata, Turris guidopoppei, Turris intercancellata, Turris kantori, T. kathiewayae. Homonymrenamed: Turris bipartita nom. nov. for Pleurotoma variegata Kiener, 1839 (non Philippi, 1836). New synonymies: Turrisankaramanyensis Bozzetti, 2006 = Turris tanyspira Kilburn, 1975; Turris imperfecti, T. nobilis, T. pulchra and T. tornatumRöding, 1798, and Turris assyria Olivera, Seronay & Fedosov, 2010 = T. babylonia; Turris dollyae Olivera, 2000 = Pleu-rotoma crispa Lamarck, 1816; Turris totiphyllis Olivera, 2000 = Turris hidalgoi Vera-Peláez, Vega-Luz & Lozano-Fran-cisco, 2000; Turris kilburni Vera-Peláez, Vega-Luz & Lozano-Francisco, 2000 = Turris pagasa Olivera, 2000; Turris(Annulaturris) munizi Vera-Peláez, Vega-Luz & Lozano-Francisco, 2000 = Gemmula lululimi Olivera, 2000. Revised sta-tus: Turris intricata Powell, 1964, Pleurotoma variegata Kiener, 1839 (non Philippi, 1836) and Pleurotoma yeddoensisJousseaume, 1883, are regarded as full species (not subspecies of Turris crispa). Neotype designated: For Pleurotoma gar-nonsii Reeve, 1843, to distinguish it from Turris garnonsii of recent authors, type locality emended to Zanzibar. New combination: Turris orthopleura Kilburn, 1983, is transferred to genus Makiyamaia, family Clavatulidae.